Historical eruptions of Avacha volcano, Kamchatka. Attempt of modern interpretation and classification for long-term prediction of the types and parameters of future eruptions. Part 2 (1926-1991) - Melekestsev I.V.; Braitseva O.A.; Dvigalo V.N.; Basanova L.I. (My University, 1994)
Previous data are summarized and new evidence is presented on the Avacha eruptions of 1926-1927, 1938, and 1945. The last eruption of January 1991 is described. The dynamics of the Avacha eruptive activity is considered for a period of 1737-1991. The eruptions are classified into different types. The type and size of a future event are predicted and the related hazard is assessed. It is recommended that the southwestern and southern sectors of the Avacha surrounding should be declared forbidden for residential or industrial construction because of a high volcanic hazard. -Journal summary
Keywords: 38.37.25 Вулканология; Авачинский